Model Sistem Dinamis Rantai Industri Tembaga di Indonesia dalam Rangka Peningkatan Nilai Tambah Ekonomi - Atika Rahmahwati; Aryo Prawoto Wibowo; Fadhila Achmadi Rosyid (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Indonesia is a leading producer of a wide range of minerals, including copper. Nonetheless, the copper-based industry in Indonesia is still not well developed, especially the limited number of products from the intermediate copper industry which will become raw materials for its downstream industry. The underdeveloped intermediate copper industry has forced Indonesia to import several types of copper-based semi-finished products to meet the needs of the downstream industry. On the other hand, the mining industry still exports copper concentrate and some copper cathodes produced by smelting. As a result, the added value obtained by Indonesia from copper is not optimal. Therefore, it is necessary to conduct research on the copper industry chain and to estimate the increase in added value that could be generated. In this study, a system dynamics (SD) model was developed. During the simulation period of 2020 to 2030, the total added value along the copper industry chain that can be obtained is USD 70,422,840,000 if the planned smelter and refinery is completed in 2023 to process all domestic concentrates and to increase intermediate industry capacity.